FUNCTIONS OF TEACHERS’ TRANSLANGUAGING IN THE EFL CLASSROOM AT TWO JUNIOR HIGH SCHOOLS IN SINGARAJA - N.M., Sapitri; I Gede, Batan; I P.N.W, Myartawan (Universitas Pendidikan Ganesha, 2018)
The use of the first language (L1) in the English as a foreign language (EFL) classroom is becoming an on-going debate. A newly growing view to the use of L1 in the foreign language (FL) classroom called translanguaging views that by utilizing the L1 along with the TL in FL classroom is considered as functional practice of languages rather than an impediment in FL learning. Accordingly it is necessary to find out the functions of teachers’ practice of translanguaging in the EFL classroom since this view has not been much researched yet. Related to this, the current study was intended to find out the functions of the EFL teachers’ translanguaging and to find out the teachers’ reasons for the use of translanguaging. This study followed qualitative descriptive interactive research design, and the subjects consisted of three English teachers at the 7th grade classes at two junior high schools in Singaraja. The data were collected through observations and interviews and were analyzed descriptive qualitatively. The results of this study showed that there were 3 functions of translanguaging. The most frequent function was related to knowledge construction, followed by classroom management, and interpersonal relations. There were 9 reasons for the teachers’ use of translanguaging, namely: to facilitate students’ understanding, to provide L1 and TL comparison, to elicit students’ responses, to attract students’ attention, tomanage students, to promote discipline, to develop deeper personal relationship, to create secure classroom atmosphere, and to make the class more interesting. In sum, the use of translanguaging plays a number of functions in the EFL classroom but it should be considered also the ‘optimal’ use of it in EFL learning process because the overuse of L1 might bring negative impact.